Impact of Conflict Resolution on the Performance of Workers of Federal Airport Authority of Nigeria (FAAN), Abuja: An Econometrics Approach - Abubakar Orlando Ijoko; Ogakwu Julius Ogbaji; Samson Galadima Simon (International Studies Journal)
This study examined the impact of conflict resolution on the performance of workers at the Federal Airport Authority of Nigeria (FAAN), Abuja. The study used the primary source of data collection, and data were collected using questionnaires that were self-administered to the staff at FAAN, Abuja. Two hundred and ninety (290) questionnaires were administered, out of which two hundred and twenty (220) were filled and returned, representing a 75% response rate. The data were exported to STATA 14.2 and were analyzed using both descriptive and inferential statistics. The major findings revealed that the collaboration strategy of conflict resolution has a positive statistical impact on the workers' performance in FAAN, Abuja. Therefore, the study recommended that the management of FAAN, Abuja, should adopt a collaborative strategy in a bid to improve the performance of workers at FAAN, Abuja.